Repair of radial artery with autogenous cephalic vein graft ınterposition after closure of arteriovenous fistula in a young renal transplantation patient: Case report - Özyüksel, Arda; Kocabeyoğlu, Sinan Sabit; Çetin, Erdem; Ünal, Ertekin Utku (Ulusal Vasküler Cerrahi Derneği, 2013)
Autogenous arteriovenous fistula at the wrist is considered as the best choice of vascular access in hemodialysis patients. In this case report, we present a young renal transplant patient who underwent autologous fistula vein interposition and closure of arteriovenous fistula to provide continuity of the radial artery

Hemodiyaliz hastalarında el bileğinde açılan otolog arteriyovenöz fistül, vasküler erişim için en iyi seçenek olarak düşünülmektedir. Bu vaka sunumunda, radiyal arterin devamlılığı sağlamak için otolog fistül ven interpozisyonu yapılan ve arterivenöz fistülü kapatılan genç renal transplantlı hasta takdim edilmiştir.
Genç renal transplantlı hastada arteriyovenöz fistül kapatılması sonrası otolog sefalik ven grefti ile radiyal arter onarımı
Keywords: Renal Dialysis; Arteriovenous Fistula; Kidney Transplantation; Böbrek Diyalizi; Arteriyovenöz Fistül; Böbrek Transplantasyonu